Visible gland constantly traces virus-induced gene silencing in cotton - Si, Zhanfeng; Wu, Huaitong; Tian, Yue; Zhang, Zhiyuan; Zhang, Tianzhen; Hu, Yan (Frontiers in Plant Science, 2022)
A virus-induced gene silencing (VIGS) system was established to induce endogenous target gene silencing by posttranscriptional gene silencing (PTGS), which is a powerful tool for gene function analysis in plants. Compared with normal plant transformation, obtaining a phenotype is fast and has high throughput in PTGS. It is low-cost and there is no need for stable plant transformation. This approach has been successfully applied to explore unknown gene functions in growth and development, physiological metabolism, and biotic and abiotic stresses in various plants. In this system, GhCLA1 was used as a general control, however, silencing of this gene leads to leaf albino, wilting, and plant death. As such, it cannot indicate the efficiency of gene silencing throughout the whole growth period. Accordingly, in this study, we developed a novel marker gene, GoPGF, as the control to trace the efficiency of gene silencing in the infected tissues. As a gland-forming gene, suppression of GoPGF does not affect normal growth and development of cotton. Moreover, we further developed a method of friction inoculation to enhance and extend the efficiency of VIGS, which facilitates the analysis of gene function in both the vegetative stage and reproductive stage. This improved VIGS technology will be an additional tool for the rapid functional identification of a large number of unknown genes in genomes.